A gel powder with high mechanical properties and its preparation method and application

By using graphene oxide and nanocellulose in 3D printing technology to prepare high-mechanical performance gel powders, the problem of insufficient mechanical properties of polymer materials is solved, and the mechanical properties and compatibility improvement of polyurethane materials are improved, forming stability 3D mesh structure to enhance the performance of composite materials.

CN118895018BActive Publication Date: 2024-12-27SUZHOU GANGRUITONG NANO MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411397524.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-27
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The mechanical properties of polymer materials in existing 3D printing technologies are limited, which limits their promotion and use in the field of machinery.

Method used

Graphene oxide and nanocellulose are used as functional fillers. By preparing graphene hydrogels and mixing them with nylon powder, nylon/nanocellulose/graphene hydrogel dispersion is formed, and high mechanical properties are formed through repeated freeze-thawing process. Glue powder, used to modify thermoplastic polyurethane materials, to improve its mechanical strength and toughness.

Benefits of technology

The mechanical properties and compatibility of polyurethane materials are significantly improved, and a stable three-dimensional mesh structure is formed, which enhances the impact load capacity and toughening of composite materials, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895018B_ABST
    Figure CN118895018B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of honeycomb materials, and specifically relates to a gel powder with high mechanical properties, a preparation method thereof and an application thereof. The preparation method of the gel powder comprises the following steps: (1) preparing a graphene hydrogel solution; (2) dissolving nylon powder in an acidic solvent, adding nanocellulose, and obtaining a nylon / nanocellulose mixed solution; (3) dripping the nylon / nanocellulose mixed solution into the graphene hydrogel solution to obtain a nylon / nanocellulose / graphene hydrogel dispersion; (4) repeatedly freezing and thawing the nylon / nanocellulose / graphene hydrogel dispersion, and finally freeze-drying and crushing the dispersion to obtain a gel powder with high mechanical properties. Nanocellulose has good compatibility with polar resins such as nylon and polyurethane. Using nanocellulose as a reinforcing filler for the gel greatly improves the interaction between graphene and polar resins such as nylon and polyurethane, thereby preventing the occurrence of brittle fracture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a gel powder with high mechanical properties and a preparation method and application thereof. Background Art

[0002] Additive manufacturing technology, also known as 3D printing, builds 3D objects by printing materials layer by layer into the desired shape. Additive manufacturing technology can create complex shapes directly from digital models, which is different from traditional manufacturing technologies. In traditional manufacturing processes, whenever a new part is made or the design of a part is changed, a new tool, mold or fixture is required. On the other hand, in 3D printing, after designing the product in the software, no structural changes in any equipment or machine are required. Therefore, 3D printing technology is changing the time-consuming and labor-intensive manufacturing process. In addition, compared with subtractive production methods, it reduces material waste and has significant advantages, including flexibility in complex geometric design, customized shapes and materials, etc. Additive manufacturing technology not only provides new ways in the field of manufacturing, but also provides new options in different industries such as biomedicine, electrical energy storage, and electronic robotics.

[0003] 3D printers with different printing technologies can use different materials. For example, a commonly used fused deposition technology 3D printer can use polymers and polymer-based composites, adding different types of fillers, including metal and ceramic nanoparticles. Among various materials, polymers are one of the most widely used raw materials in almost all types of 3D printing methods. Depending on the printing method and application, different types of polymers, including thermoplastics and photosensitive polymers, can be customized to suit the manufacturing process.

[0004] Thermoplastic polyurethane (TPU) is a high molecular polymer with elasticity. TPU has good comprehensive properties, such as high deformation rate, strong toughness, low wear resistance and flexibility. The molecular structure of polyurethane includes hard segments and soft segments, which produce microphase separation due to their different polarities. Therefore, this separation affects the flexibility of the molecule and the crystallization of the hard segment. In this case, TPU obtains its rigidity and hardness from the crystalline domain of the hard segment, while the non-crystalline soft segment provides its flexibility and elastic behavior.

[0005] With the development of 3D printing technology, more and more consumables are suitable for 3D printing. Polyurethane materials are a good source of 3D printing consumables due to their excellent wear resistance, low-temperature flexibility, high toughness, excellent corrosion resistance and a wide range of available mechanical strength. In recent years, the 3D printing technology for polyurethane materials has been continuously updated, and 3D printed polyurethane products have also been increasingly recognized and applied. 3D printing avoids designing molds, and small-batch production is more time-efficient. At the same time, it diversifies product models and has been widely used in various fields. However, due to the restrictions on the types of polymer materials used in 3D printing, its mechanical properties have not been improved on a large scale, limiting its promotion and use in the mechanical field. Summary of the invention

[0006] The purpose of the present invention is to provide a gel powder with high mechanical properties and a preparation method and application thereof, which not only simplifies the preparation process but also greatly improves the mechanical strength and toughness of the polyurethane material modified by the gel powder.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0009] (1) dispersing graphene oxide and a reducing agent in deionized water to obtain a graphene oxide mixed solution, sealing the solution and heating the solution to obtain a graphene hydrogel solution;

[0010] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:(0.05-0.5):(0.1-3);

[0011] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0012] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties.

[0013] Aerogel is a light and highly porous solid material with a high specific surface area and easy modification. It is often added to the matrix material as a functional filler. Graphene aerogel has the characteristics of low density, high porosity, good resilience and adsorption, and is a widely used inorganic aerogel modified material. Existing graphene aerogel-based polymer composite materials are generally prepared by preforming-impregnation filling method and polymer cross-linking self-assembly method. For example, CN107674421A and CN109810499A respectively prepared composite materials by aerogel preforming and self-assembly process. The above process requires the addition of a large amount of resin matrix to construct a stable gel network, which seriously affects the pore size and porosity of the aerogel itself, resulting in the prepared aerogel being unable to be used as a functional filler. In order to solve this problem, the present invention first prepares graphene hydrogel, constructs a gel skeleton structure, and then adds a nylon / nanocellulose mixed solution to prepare nylon / nanocellulose / graphene hydrogel. The inventor used carbon nanotubes as a conductive reinforcing filler for gel in previous work. Although carbon nanotubes have high electrical conductivity, they are inorganic fillers and have poor compatibility with nylon and polyurethane. When subjected to high external forces, carbon nanotubes and the resin matrix are prone to peeling at the interface between the two phases due to low interfacial forces, which is not conducive to improving the mechanical properties of the composite material.

[0014] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood. Nanocellulose itself has excellent nano-size effect, reactivity and large specific surface area. Nanocellulose has a large number of intramolecular and intermolecular hydrogen bond networks, which are tightly and orderly stacked to provide cellulose with high stiffness and strength; at the same time, the distance between nanocellulose molecules is large, and the molecular chains are free and loose, which gives cellulose high flexibility. The graphene hydrogel prepared in advance plays the role of matrix, and the nanocellulose added later has better flexibility than carbon nanotubes, and can be easily immersed in the hydrogel to form, and further form a network structure inside or on the surface of the hydrogel, which plays a role in dispersing stress. Furthermore, nanocellulose contains rich surface hydroxyl groups and has good compatibility with polar resins such as nylon and polyurethane. Using nanocellulose as a reinforcing filler for the gel greatly improves the interaction between graphene and polar resins such as nylon and polyurethane, and prevents the occurrence of brittle fracture. Furthermore, when the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:(0.05-0.5):(1-2), the nanocellulose modification effect is optimal; it can not only play its connecting role, but also avoid excessive nanocellulose affecting the formation of the gel structure.

[0015] The present invention adds nanocellulose to the mixed solution of nylon, effectively improving the compatibility between nanocellulose and graphene; and, when the prepared nylon / nanocellulose / graphene aerogel is used for 3D printing thermoplastic polyurethane materials, since the amide bonds in nylon and the hydroxyl groups in nanocellulose form a large number of hydrogen bonds with the urethane bonds in polyurethane, they can serve as a connecting bridge to improve the compatibility of graphene / nanocellulose and polyurethane, and overcome the defect of low interfacial force of carbon nanotubes. As a resin additive for graphene / nanocellulose, nylon improves the mechanical properties of the aerogel itself on the one hand; on the other hand, it improves the compatibility of aerogel and thermoplastic polyurethane materials, and can promote the dispersion of gel powder in thermoplastic polyurethane during 3D printing. Nylon resin does not need to be modified by an in-situ polymerization process, and can be directly dissolved and blended with nanocellulose, simplifying the production process.

[0016] Moreover, the present invention obtains a mixed hydrogel by repeatedly freezing and thawing a nylon / nanocellulose / graphene hydrogel dispersion. Through the repeated freezing and thawing process, the blending of nanocellulose, nylon resin and inner graphene is promoted, and the binding force between the three is enhanced. More importantly, since nanocellulose has better flexibility than carbon nanotubes, it will curl up and cross-link with each other during the repeated freezing and thawing process, forming an interlaced network structure on the outer surface of the gel. When used in a 3D printing process, the interface with polyurethane is increased, and a stable three-dimensional network structure is formed by mutual entanglement with polymer molecular chains, so that the composite material can withstand a certain degree of impact load, and plays a certain role in the toughening of the composite material.

[0017] Furthermore, in step (1), the graphene oxide concentration in the graphene oxide mixed solution is 1-2 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:(0.1-0.5).

[0018] Furthermore, in step (1), the reaction temperature is 60-90° C. and the reaction time is 1-4 h.

[0019] Furthermore, in step (2), the nylon is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212.

[0020] Furthermore, in step (2), the acidic solvent is at least one of formic acid and sulfuric acid.

[0021] Furthermore, the nanocellulose in step (2) is plant-based nanocellulose. The main source of nanocellulose is plant-based biomass, including wood, bamboo, hemp, palm trees, etc. The present invention uses nanocellulose obtained from sisal as biomass.

[0022] Furthermore, the repeated freezing and thawing in step (4) is freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0023] On the other hand, the present invention also provides an application of high mechanical performance gel powder, which is used in the field of 3D printing polyurethane materials; the 3D printing polyurethane material contains the following components by weight: 100 parts of thermoplastic polyurethane elastomer; 5-20 parts of high mechanical performance gel powder; 1-5 parts of flow modifier. The modified gel powder has high mechanical strength, large specific surface area, and high Young's modulus; and the fiber network of the mesh structure distributed on the outer layer increases the interaction area with polyurethane, making it a compatibility enhancement material with great development potential.

[0024] Beneficial effects: The present invention first prepares graphene hydrogel, constructs a gel skeleton structure, and then adds a nylon / nanocellulose mixed solution to prepare a nylon / nanocellulose / graphene hydrogel. The graphene hydrogel prepared in advance acts as a matrix, and the subsequently added nanocellulose has better flexibility than carbon nanotubes, and can be easily immersed in the hydrogel for molding, and further forms a network structure inside or on the surface of the hydrogel, which plays a role in dispersing stress. Furthermore, nanocellulose contains abundant surface hydroxyl groups and has good compatibility with polar resins such as nylon and polyurethane. Using nanocellulose as a reinforcing filler for the gel greatly increases the interaction between graphene and polar resins such as nylon and polyurethane, thereby preventing the occurrence of brittle fracture.

[0025] The repeated freezing and thawing process promotes the blending of nanocellulose, nylon resin and inner graphene, and enhances the bonding force between the three. More importantly, since nanocellulose has better flexibility than carbon nanotubes, it will curl up and cross-link during the repeated freezing and thawing process, forming an interlaced network structure on the outer surface of the gel. When used in the 3D printing process, it increases the interface with polyurethane, and forms a stable three-dimensional network structure through mutual entanglement with the polymer molecular chains, so that the composite material can withstand a certain degree of impact load and play a certain role in the toughening of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the high mechanical properties gel powder prepared in Example 7;

[0027] Figure 2 This is a scanning electron microscope image of the nylon / carbon nanotube / graphene aerogel prepared in Comparative Example 1. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0029] Example 1

[0030] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0031] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.1; the reaction temperature is 60°C, and the reaction time is 3.5 h;

[0032] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.05:1; the nylon is nylon 66; and the acidic solvent is formic acid;

[0033] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0034] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0035] A 3D printing polyurethane material comprises the following components in parts by weight:

[0036] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0037] Example 2

[0038] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0039] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 2 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.5; the reaction temperature is 90°C, and the reaction time is 1.2 h;

[0040] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.5:2; the nylon is nylon 66; and the acidic solvent is formic acid;

[0041] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0042] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0043] A 3D printing polyurethane material comprises the following components in parts by weight:

[0044] 100 parts of thermoplastic polyurethane elastomer; 14 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0045] Example 3

[0046] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0047] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.5; the reaction temperature is 60°C, and the reaction time is 3 h;

[0048] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.5:1; the nylon is nylon 66; and the acidic solvent is formic acid;

[0049] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0050] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0051] A 3D printing polyurethane material comprises the following components in parts by weight:

[0052] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0053] Example 4

[0054] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0055] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 2 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.1; the reaction temperature is 90°C, and the reaction time is 1.6 h;

[0056] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.05:1.6; the nylon is nylon 66; and the acidic solvent is formic acid;

[0057] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0058] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0059] A 3D printing polyurethane material comprises the following components in parts by weight:

[0060] 100 parts of thermoplastic polyurethane elastomer; 16 parts of high mechanical performance gel powder; 3 parts of zinc stearate.

[0061] Example 5

[0062] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0063] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.7 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 80°C, and the reaction time is 2 h;

[0064] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.15:1.3; the nylon is nylon 66; and the acidic solvent is formic acid;

[0065] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0066] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0067] A 3D printing polyurethane material comprises the following components in parts by weight:

[0068] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 2 parts of zinc stearate.

[0069] Example 6

[0070] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0071] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.7 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 70°C, and the reaction time is 2.8 h;

[0072] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.4:1.8; the nylon is nylon 66; and the acidic solvent is formic acid;

[0073] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0074] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0075] A 3D printing polyurethane material comprises the following components in parts by weight:

[0076] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 1 part of zinc stearate.

[0077] Example 7

[0078] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0079] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.4 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 80°C, and the reaction time is 2.2 h;

[0080] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.2:1.4; the nylon is nylon 66; and the acidic solvent is formic acid;

[0081] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0082] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0083] A 3D printing polyurethane material comprises the following components in parts by weight:

[0084] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0085] Example 8

[0086] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0087] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.4 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 80°C, and the reaction time is 2.2 h;

[0088] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.2:0.5; the nylon is nylon 66; and the acidic solvent is formic acid;

[0089] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0090] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0091] A 3D printing polyurethane material comprises the following components in parts by weight:

[0092] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0093] Example 9

[0094] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0095] (1) Graphene oxide and a reducing agent are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to react to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.4 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 80°C, and the reaction time is 2.2 h;

[0096] (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.2:3; the nylon is nylon 66; and the acidic solvent is formic acid;

[0097] (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0098] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0099] A 3D printing polyurethane material comprises the following components in parts by weight:

[0100] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0101] Comparative Example 1

[0102] A method for preparing nylon / carbon nanotube / graphene aerogel comprises the following steps:

[0103] (1) Adding graphene oxide to deionized water to obtain a graphene oxide dispersion, adding a reducing agent to the graphene oxide dispersion, ultrasonically treating, and sealing the reaction to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide dispersion is 1.6 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.3; the ultrasonic time is 0.8 h; the reaction temperature is 80 ° C, and the time is 2 h;

[0104] (2) Dissolving nylon powder in a solvent, then adding multi-walled carbon nanotubes, and stirring evenly to obtain a nylon / carbon nanotube mixed solution; the mass ratio of graphene oxide, nylon powder, and carbon nanotubes is 1:0.2:1.6; the nylon is nylon 66; and the solvent is formic acid;

[0105] (3) under stirring conditions, adding the nylon / carbon nanotube mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / carbon nanotube / graphene hydrogel dispersion;

[0106] (4) The nylon / carbon nanotube / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a nylon / carbon nanotube / graphene aerogel; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0107] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of nylon / carbon nanotube / graphene aerogel; and 4 parts of zinc stearate.

[0108] Comparative Example 2

[0109] A method for preparing a gel powder with high mechanical properties comprises the following steps:

[0110] (1) Graphene oxide, a reducing agent and nanocellulose are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and heated to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1.4 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the reaction temperature is 80°C and the reaction time is 2.2 h;

[0111] (2) dissolving nylon powder in an acidic solvent and stirring the mixture to obtain a nylon mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:0.2:1.4; the nylon is nylon 66; and the acidic solvent is formic acid;

[0112] (3) under stirring conditions, adding the nylon mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion;

[0113] (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties; the repeated freezing and thawing is performed by freezing in a refrigerator for 10 hours and then thawing at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

[0114] A 3D printing polyurethane material comprises the following components in parts by weight:

[0115] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high mechanical performance gel powder; 4 parts of zinc stearate.

[0116] Comparative Example 3

[0117] The preparation method is basically the same as that of Example 7, except that the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:1:1.4.

[0118] Performance test: The 3D printed polyurethane materials in Examples 1-9 and Comparative Examples 1-3 were printed into strips, and the tensile properties of the strips were tested with reference to GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.

[0119]

[0120] Figure 1 This is a scanning electron microscope image of the high mechanical properties gel powder prepared in Example 7; it can be seen from the figure that the fibers form a cross-shaped mesh structure. It can be seen that nanocellulose has better flexibility than carbon nanotubes. During repeated freezing and thawing, it will curl up and cross-link with each other, forming a staggered mesh structure on the outer surface of the gel. When used in the 3D printing process, it increases the interface with polyurethane, and forms a stable three-dimensional mesh structure through mutual entanglement with the polymer molecular chains, so that the composite material can withstand a certain degree of impact load and play a certain role in the toughening of the composite material. Figure 2The scanning electron microscope image of the nylon / carbon nanotube / graphene aerogel prepared in Comparative Example 1 shows that the carbon nanotubes are dispersed and arranged, and do not form an interlaced structure, and the reinforcing effect is limited. As can be seen from Table 1, the graphene hydrogel prepared in advance plays the role of a matrix, and the nanocellulose added subsequently has better flexibility than the carbon nanotubes, and can be easily immersed in the hydrogel for molding, and further forms a network structure inside or on the surface of the hydrogel, which plays a role in dispersing stress. Furthermore, nanocellulose contains abundant surface hydroxyl groups and has good compatibility with polar resins such as nylon and polyurethane. The use of nanocellulose as a reinforcing filler for the gel greatly improves the interaction between graphene and polar resins such as nylon and polyurethane, and prevents the occurrence of brittle fracture. Comparative Example 1 is the carbon nanotubes used by the inventor as a reinforcing filler, and its mechanical properties are limited. Comparative Examples 2-3 show that the post-addition of nanocellulose can play a bridging role, embedding the gel powder into the polyurethane and improving the mechanical properties; however, when the amount of nanocellulose added is too much, it will affect the infiltration of the gel powder by thermoplastic polyurethane during 3D printing, which is not conducive to the improvement of mechanical properties.

[0121] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.

Claims

1. A method for preparing a gel powder with high mechanical properties, characterized in that: The following steps are involved: (1) dispersing graphene oxide and a reducing agent in deionized water to obtain a graphene oxide mixed solution, sealing and heating the solution to obtain a graphene hydrogel solution; the mass ratio of graphene oxide to reducing agent is 1:(0.1-0.5); the reaction temperature is 60-90°C, and the reaction time is 1-4h; (2) dissolving nylon powder in an acidic solvent, then adding nanocellulose and stirring evenly to obtain a nylon / nanocellulose mixed solution; the mass ratio of graphene oxide, nylon powder and nanocellulose is 1:(0.05-0.5):(0.1-3); (3) under stirring conditions, adding the nylon / nanocellulose mixed solution dropwise into the graphene hydrogel solution to prepare a nylon / nanocellulose / graphene hydrogel dispersion; (4) The nylon / nanocellulose / graphene hydrogel dispersion is repeatedly frozen and thawed to obtain a mixed hydrogel, which is then freeze-dried and crushed to obtain a gel powder with high mechanical properties.

2. The method for preparing a gel powder with high mechanical properties according to claim 1, characterized in that: Step (1) The graphene oxide concentration in the graphene oxide mixed solution is 1-2 mg / mL; and the reducing agent is ascorbic acid.

3. The method for preparing a gel powder with high mechanical properties according to claim 1, characterized in that: In step (2), the nylon is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212.

4. The method for preparing a gel powder with high mechanical properties according to claim 1, characterized in that: In step (2), the acidic solvent is at least one of formic acid and sulfuric acid.

5. The method for preparing a gel powder with high mechanical properties according to claim 1, characterized in that: The nanocellulose in step (2) is plant-based nanocellulose.

6. The method for preparing a gel powder with high mechanical properties according to claim 1, characterized in that: The repeated freezing and thawing in step (4) is to freeze in a refrigerator for 10 hours and then thaw at room temperature for 10 hours, and the freezing / thawing process is repeated 4 times.

7. A gel powder with high mechanical properties, characterized in that: The invention is prepared by the preparation method of a gel powder with high mechanical properties as described in any one of claims 1 to 6.

8. An application of the high mechanical properties gel powder as claimed in claim 7, characterized in that: Use high mechanical properties gel powder in the field of 3D printing polyurethane materials.

9. A 3D printing polyurethane material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 5-20 parts of high mechanical property gel powder; 1-5 parts of flow modifier; the high mechanical property gel powder is the high mechanical property gel powder according to claim 7.

Citation Information

Patent Citations

  • Method for preparing graphene / carbon nanotube aerogel polymer conductive composite material and application thereof

    CN107674421A

  • Preparation method of nylon / carbon nanotube aerogel

    CN109810499A

  • Graphene aerogel three-dimensional structure and preparation method thereof

    CN110697692A

  • Three-dimensional molding material, three-dimensional object, and slice layer of three-dimensional object

    CN111978707A